2022
DOI: 10.2174/1568026622666220105104355
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Content and Potential Health Applications of Pecan [Carya illinoinensis (Wangenh) K. Koch] Nutshell

Abstract: Background: The pecan nutshell contains phytochemicals with various biological activities that are potentially useful in the prevention or treatment of diseases such as cancer, diabetes, and metabolic imbalances associated with heart diseases. Objective: To update this topic by means of a literature review and include those that contribute to the knowledge of the chemical composition and biological activities of pecan nutshell, particularly of those related to the therapeutic potential against some chronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
0
0
Order By: Relevance
“…Carya illinoinensis is an important economic forest species, and its fruit has high nutritional values [18]. To date, endophytic fungi in C. illinoinensis and their function have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Carya illinoinensis is an important economic forest species, and its fruit has high nutritional values [18]. To date, endophytic fungi in C. illinoinensis and their function have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Un compuesto bioactivo es simplemente una sustancia que tiene una actividad biológica, relacionada con su capacidad para modular uno o más procesos metabólicos, lo que resulta en la promoción de mejores condiciones de salud (Dictionary, 2009) (Aryee & Boye, 2015). En el caso de la nuez pecanera numerosos documentos de investigación indican el potencial de su cáscara en la obtención de fitocompuestos como polifenoles, flavonoides y taninos asociados con diversas actividades biológicas, entre las que destacan: antimicrobianas, anticancerígenas, antidiabéticas y antioxidantes, entre otras (Reyes et al,2022) Los antioxidantes son considerados agentes protectores que inactivan las especies reactivas de oxígeno, por lo que previenen el daño oxidativo. Entre las enzimas involucradas en contrarrestar el estrés oxidativo se encuentran el superóxido dismutasa, catalasa y glutatión peroxidasa, las cuales atenúan las especies reactivas de oxígeno generadas por el metabolismo.…”
Section: Introductionunclassified
“…[8]. Pecan contains various phytochemicals, which have medicinal value in various diseases [9]. The kernel contains multiple phenolic compounds, giving pecan strong antioxidant properties It is reported that pecan phenolic compounds, which have antioxidant activity can reduce the risk of cancer, Alzheimer, Parkinson and the other degenerative diseases [10].…”
Section: Introductionmentioning
confidence: 99%